Організація інформаційно-довідкового забезпечення органів місцевого самоврядування - Химиця, Наталія; Сувала, Оксана (Видавництво Львівської політехніки, 2019)
In the article the problem of information representative bodies to ensure feedback between citizens and the state, analyzed public relations as a mechanism of interaction between the state and civil society, , and generally describes the functionality of the web – sites of public authorities at regional level.
Keywords: інформація; органи влади; органи місцевого самоврядування; громада; інформаційне забезпечення; звернення громадян; довідкова інформація; зв’язки з громадськістю